Experience of moral distress by personality: theoretical understanding of the problem - Fedotova, Tetiana (Psychological Prospects Journal, 2022)
The purpose of the article is to theoretically analyze the problem of moral distress in the scientific literature, to clarify the main aspects of the study of the relevant issues and to establish the features of the manifestation of moral distress by secondary analysis of the results of empirical research of scientists. Methods. The article uses the methods of theoretical study of scientific literature (analysis, synthesis, generalization, systematization of approaches of scientists) in relation to the coverage of the problem of experiencing moral distress. Results. The problems of moral distress in the scientific literature are covered mainly by studying it in the course of the professional activity of medical workers. Moral distress is considered as moral suffering that arises in a person in a situation of knowledge about how to act, but the inability to act accordingly, due to the established institutional restrictions. There are types of moral distress: primary (described as moral distress itself) and reactive (considered as "moral residue"). The empirical markers of moral distress are: feelings of anger, frustration and guilt, inability to translate moral judgment into action, self-doubt, lack of perseverance, conformism, perceived powerlessness, lack of criticality and understanding of the situation, etc. The physical consequences of prolonged moral distress for the individual may include insomnia, nausea, migraines, gastrointestinal disorders, tearfulness and significant physical exhaustion. According to scientists, moral judgment/necessity of choice, institutional/legal constraint, psychological effect/influence, moral conflict, threat to moral integrity and authenticity, internal constraints and moral climate of the institution can be a necessary and/or sufficient condition for experiencing moral distress. In unity with the theory of moral distress, the theory of moral reckoning is considered, the core of which is the analysis of the experience of moral reckoning by a nurse: ease, situational binding, solution and reflection. Conclusions. The theoretical analysis of the problem of moral distress has shown the complexity and ambiguity in the definition of the relevant concept, its indicators and factors. The theoretical study of this issue indicates the expediency and importance of a thorough study of moral distress, taking into account age, gender and professional aspects, as well as the relevance and necessity of developing a program of psychological support for people experiencing moral distress, a set of measures to preserve the mental health of vulnerable groups in the context of hostilities.